Predictors of Job Satisfaction in Dental Professionals of the Bosnia and Herzegovina Federation - Edin Muhić; Darije Plančak; Vlatka Lajnert; Asja Muhić (University of Zagreb. School of Dental Medicine, 2016)
Introduction: Working in a healthy work environment is the ultimate goal of every employee. Dentistry is a stressful career, and the reasons for dissatisfaction are numerous. Aim: The aim of this study was to determine the factors of work satisfaction in dental professionals of the Bosnia and Herzegovina Federation. Materials and methods: A total of 134 dental professionals selected randomly from the Registry of Dental Chamber of Bosnia and Herzegovina Federation were included in the study. All of them filled out the Demographic Questionnaire and Job Satisfaction Scale (JSS). Results: An increase in the influence of work on the quality of life as well as an increase in its frequency results in leaving the job and significantly reducing the overall job satisfaction. General dental practitioners are significantly more satisfied as compared with specialists. Significant predictors of the job satisfaction are employment status, type of the practice, and availability of dental assistants. General dental practitioners with a dental assistant employed at a private practice are more likely to be satisfied with their jobs. Conclusions: Employment status, practice type and availability of dental assistants are significant predictors of job satisfaction. General dental practitioners working in a private practice with a dental assistant are most likely to be satisfied.